TRADITIONAL MEDICINES AMONG THE EMBU AND MBEERE PEOPLES OF KENYA - Kareru, P. G.; Kenji, G. M.; Gachanja, A. N.; Keriko, J.M.; Mungai, G. (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
Ethnobotanical information and traditional medicines were investigated and documented in Embu and Mbeere districts, Eastern Province of Kenya. Oral interviews were obtained from over 100 herbalists, both men and women aged between 40 and 80 years. All the herbalists interviewed were Christians and had little formal education. Non-Christian herbalists were purported to combine herbal medicines with witchcraft and were not interviewed. Of the 40 commonly used herbal plants 25 were used as multi-purpose medicinal plants (mpmp), while 15 were used to treat one disease type. There was a correlation between the outpatient morbidity data at the local District hospital, and the common incident diseases treated by the herbalists. Generally a decoction or infusion of the herb was recommended for the treatment of internal or external condition of the patients. Malaria and typhoid were treatable with a total of 15 and 12 plants respectively and were among the first two commonest diseases found in the study area. Terminalia brownii was found to be the most used medicinal plant either alone or in combination with other herbs. The second and third most utilized medicinal plants were Ovariodendron anisatum and Wurbugia ugadensis respectively.